Strategi Intervensi Sosial Mikro dalam Mengatasi Individu dengan Gangguan Bipolar - Nasywa Faza Lailan; Ati Kusmawati; Ananda Zahra; Alya Rukmana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The phenomenon of bipolar disorder is one serious public health problem, for it can lower the quality of life of an individual and increase the high risk of death. Bipolar is a fluctuating mood or mood condition-changing from mania (higher) to depression. The study will explore effective microsocial intervention strategies in addressing individuals with bipolar disorder, taking into account the social, emotional, and environmental factors that can affect the management of those conditions. The study USES a descriptive qualitative method of study with data gathered in words, pictures, not Numbers. By understanding the microsocial dynamics affecting individuals with bipolar disorder, we can devise interventions that are more relevant and effective, creating supportive environments and helping to address their welfare